Psychometer characteristics (honesty and fortitude) of the psychological stress scale of asample of university professors- Field study at Mohammed Boudiaf University - Abdelli, Rabiaa; Djaalab, Nourdine (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2024)
The current study aimed to build a psychometer that has the characteristics of a good scale, and to ascertain its psychometric characteristics, a sample of 60 professors and professors from the Faculty of Humanities and Social Sciences was selected for both (Psychology Department, Sociology Department, Media and Communication Department, History Department, Sharia Department, Philosophy Department) The Faculty of Literature and Languages of the Department of Arabic Language and Literature, and to verify the psychometric characteristics of the scale were used statistical methods: The Pearson correlation coefficient and the A-Crumbach laboratory, after statistical treatment, was communicated to the following results of the statistical analysis of the data having three dimensions of the psychological stress metric: The psychological dimension is physical, after the working environment, and the behavioral dimension, as the results of the study showed that the scale prepared has high psychometric characteristics, This indicates that the psychological stress scale has a high degree of honesty. and with the same stability, this is evidenced by two important indicators One is the coherence of each dimension of the scale as a whole, and the other is the coherence of the three dimensions combined. By taking the values of the Alpha Kronbach coefficient in each of the three dimensions of the scale, it is characterized by a high degree of stability confirmed by the values obtained, which indicate the harmony between the paragraphs and the dimension to which they belong. Based on the results of the study, the psychological stress scale has good